EFEKTIVITAS PROGRAM USAHA EKONOMI DESA SIMPAN PINJAM (UED-SP) DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT DESA SAWAH KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR. - Yuliani, Febri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is based on several inappropriate Loaning Economic Program (UED-SP) allocations both in the side of bureaucrats or loaners. Sinar Dana UED-SP implementation in terms of giving the loan to the people tends to focus on its orientation of loaner’s ability to return. Meanwhile it should have focused on people’s economic condition and level of entreprises developing nessecity. In addition, some of the loaners do not allocate its fund appropriately which they should have done underway as this program’s objective that is to develop their entreprises yet to another consumptive usages. Both Bureaucrats or people should cooperate one another to UED-SP Program not only to its fund returning development but also loaners’ entreprise development regarding and poor people empowerment. Enhance, the main objective of UED-SP implementation that is to empower society will flourishingly be achieved.The concept of theory is efectivity, revealed by Mahmudi. This research is using qualitative method which analysis the data through describing explaination. Researcher is collecting the data by interview, observation and documentation which use key informan as information resource and triangulation technic measuring its validity of data.As a result of this research that the implementation of Sinar Dana UED-SP Program in Desa Sawah has not been implemented effectively. Although this program has been running and its fund developed well. Yet, the main objective of this program which is aiming to empower poor people. One of the main factor which become a barrier to this program achievement is the terms and conditions of entreprise capital loaning, those are returning guarantee which is not affordable to the middle low economic society.Keywords : Efectivity, Saving and Loaning Village’s Economic Entreprise (UED-SP), Empowerment